Pengembangan Paket Bimbingan Konseling Covid-19 Berbasis Ajaran Islam dan Dakwah serta Pengaruhnya dalam Mencegah Penyebaran Covid di Kota Makassar - Abdul Hadis; Nurhayati B; Usman Usman (Seminar Nasional LP2M UNM, 2022)
Abstrak. The  fact  shown that  distributed  Covid-19  infection  to  the  peoples  of  Makassar  City  not  yet  final.  This  caused  application,  understanding,  and  knowledge  of  peoples  is  low  about  cleaning  and  dangerous  of  Covid-19.  Therefore,  the  goal  of  this  research  is  for  product  of  counseling  and  guidance  Covid-19  based  dakwah  dan  Islam.  From  this  development  research,  opportunited  fist  year  birth  product  Covid-19  Counseling  and  Guidance  dan  at  second  year  of  this  research  is  experimentation  this  product  fot  konow  effect  to  preventive  distribution  infection  of  Covid-19.  This  research  design  is  development  research  with  adoption  of    Dick  and  Carey  model  pasca  adaptation  by  researchers  team Kata Kunci: Counseling  and  guidance,  Covid-19,  Islam  and  Dakwah